2016
DOI: 10.1117/1.jpe.6.045502
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of highly reproducible polymer solar cells using ultrasonic substrate vibration posttreatment

Abstract: "Fabrication of highly reproducible polymer solar cells using ultrasonic substrate vibration posttreatment," J. Photon. Energy 6(4), 045502 (2016), doi: 10.1117/1.JPE.6.045502. Abstract. Organic solar cells are usually nonreproducible due to the presence of defects in the structure of their constituting thin films. To minimize the density of pinholes and defects in PEDOT:PSS, which is the hole transporting layer of a standard polymer solar cell, i.e., glass/ ITO/PEDOT:PSS/P3HT:PCBM/Al, and to reduce scattering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Although the aforementioned chemical methods can improve the conductivity of PEDOT:PSS films, a facile, low-cost, and environmentally friendly mechanical technique is more appealing. In this context, Eslamian and coworkers [40][41][42][43][44] demonstrated remarkable improvement in almost all characteristics of PEDOT:PSS thin films by imposing ultrasonic vibration on the substrate and the wet film during or after the deposition process by spin or spray coating. In the case of spray-on PEDOT:PSS films [40] and PEDOT:PSS/graphene composite films [45,46], it was observed that employing ultrasonic vibration promotes solution mixing and film surface levelling, due to a mild instability caused by the vibration [45,46], resulting in a more uniform and conductive PEDOT:PSS thin film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the aforementioned chemical methods can improve the conductivity of PEDOT:PSS films, a facile, low-cost, and environmentally friendly mechanical technique is more appealing. In this context, Eslamian and coworkers [40][41][42][43][44] demonstrated remarkable improvement in almost all characteristics of PEDOT:PSS thin films by imposing ultrasonic vibration on the substrate and the wet film during or after the deposition process by spin or spray coating. In the case of spray-on PEDOT:PSS films [40] and PEDOT:PSS/graphene composite films [45,46], it was observed that employing ultrasonic vibration promotes solution mixing and film surface levelling, due to a mild instability caused by the vibration [45,46], resulting in a more uniform and conductive PEDOT:PSS thin film.…”
Section: Introductionmentioning
confidence: 99%
“…Eslamian [47] also reviewed conventional and emerging applications of ultrasonic vibration in various configurations and systems. The aforementioned works [40][41][42][43][44] were performed with a single frequency of 40 kHz on films coated on glass substrates. Owing to the potential of the method, in this work, we carefully characterized the response of the ultrasonic transducers and systematically investigated the effect of varying ultrasonic vibration frequency and power on characteristics of spun PEDOT:PSS thin films, to gain further insight and also obtain optimum conditions from a practical point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Another important topic in emerging FETs is the stability of the solution-processed layers and the device hysteresis when subjected to a pulsed gate voltage over multiple cycles [11]. While the topic was not studied in this work, in [2] and [42] we have demonstrated that the application of the ultrasonic vibration on the active layers has a remarkable effect on the stability of the films used in polymer and perovskite solar cells, respectively.…”
Section: Perovskite Fetmentioning
confidence: 77%
“…Poly(3-hexylthiophene) (P3HT) and methylammonium lead iodide (CH 3 NH 3 PbI 3 ) perovskite are employed as the solution-processed semiconducting channels. P3HT has been used extensively in organic photovoltaics (OPV) [2] and OFETs [1,[3][4][5][6][7][8]. Perovskites, which have been extensively used in perovskite solar cells [9,10], have been recently employed in the area of thin film FETs to develop high performance devices.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this study, a novel, facile, low-cost, and more repeatable mechanical approach, termed as ultrasonic substrate vibration post treatment (SVPT), is employed to control the crystal growth and to improve the interfacial contacts between the perovskite and m-TiO 2 layers. The application of the SVPT method on organic [20,21] and perovskite [22] solar cells has shown that imposing low-amplitude ultrasonic vibration on the wet thin films results in an improvement in the film nanostructure and the device reproducibility, because it promotes the evaporation rate [23] and causes micromixing of the solution components [24,25]. However, in the aforementioned studies, the effect of the imposed vibration on the crystallization of the perovskite precursor solutions deposited on a mesoporous layer, such m-TiO 2 layer, has not been investigated.…”
Section: Introductionmentioning
confidence: 99%